Essential Hard skill For Student in VUCA Era: Literature Study - Andri Soemitra; Anggia Sari Lubis; Ratna Sari Dewi; Debbi Chyntia Ovami (Journal of Trends Economics and Accounting Research, 2023)
The purpose of this article is to provide a literature study of essential hard skill for students in Volatility, Uncertainty, Complexity and Ambiguity (VUCA) era. The authors aim to base their new conceptualization on extensive evidence from literature review, and synthesis of the review of literature. An extensive literature review of essential hard skill for student in VUCA era is first carried out. Based on the review and synthesis of literature, an essential hard skill for student in VUCA era with three domain areas is conceptualized. The higher education curricula can now apply more specifically, any of the three dimensions areas of essential hard skill for student in VUCA era and understand the conditions under which a particular dimensions area is important for students to understand the changes caused by the VUCA and adjust the hard skills possessed by these changes.